Voting experience in a new era: The impact of past eligibility on the breakdown of mainstream parties - Fernando De la Cuesta (Research & Politics)
This paper studies the influence of the context in shaping the effects on later voting behavior of first experiences with voting. I leverage from changes in the political context in Spain produced by the Great Recession to answer whether individuals’ first voting experience affects the electoral support for mainstream parties differently depending on the different political context that first voters experienced before and after the Great Recession. I use a novel database of pre-electoral surveys between 2000 and 2015 and a difference-in-differences analysis. I exploit the exogenous variation produced by the legal voting-age threshold in Spain (18 years-old) among people of the same cohort. I find that, after the Great Recession, second-time eligibility voters have a higher probability to vote for mainstream forces than their counterfactual equals. The results show that, in a context of political change, first voting experience strengthens the vote for mainstream parties. The results show that previous voting experience creates favorable inertia for mainstream parties that slow down the change of a political system.